Extended aeration : a comparative study between prefabricated reinforced fiberglass and concrete cast in-situ plants - Abdul Razik, Mohd. Shukri (2007)
The choice of wastewater treatment plants for any application depends on the quality of raw sewage, the required quality of treated water and the economics resources available to pay for both capital cost and operating cost of the treatment plants. The performance of any wastewater treatment plants does not only depend on the construction cost but will also cover the cost and method of operation and maintenance, quality of effluent treated, internal, external and design factors. While potential for identifying a better type of wastewater treatment plant does exist, very modest efforts have been attempted. This study compares and contrasts two of the most commonly used extended aeration systems for small to medium size sewage treatment plants, namely prefabricated reinforced fibreglass and cast in-situ systems. The selected treatment plants are under the jurisdiction of Indah Water Konsortium Sdn. Bhd. (IWK), Terengganu. The flow of raw sewage and the performance of the treatment plants based on effluent quality (i.e. BOD, COD and SS) and electricity cost were assessed. Three treatment plants from both types of systems were studied for a period of five months. It was found that a small to medium size treatment plants suffer high variation in term of flow and organic loading. It seemed obvious that the cast in-situ treatment plants not only built structurally better and ease of operation, but also giving better effluent standard and consumed lower electricity cost.